In situ probing of the crystallization kinetics of rr-P3HT on single layer graphene as a function of temperature. Issue 12 (13th March 2017) - Boulanger, Nicolas; Yu, Victor; Hilke, Michael; Toney, Michael F.; Barbero, David R.
Abstract : In situ X-ray diffraction analysis of P3HT films during cooling down on both Si and G. Abstract : We studied the molecular packing and crystallization of a highly regio-regular semiconducting polymer poly(3-hexylthiophene) (P3HT) on both single layer graphene and silicon as a function of temperature, during cooling from the melt. The onset of crystallization, crystallites' size, orientation, and kinetics of formation were measured in situ by synchrotron grazing incidence X-ray diffraction (GIXD) during cooling and revealed a very different crystallization process on each surface. A favored crystalline orientation with out of plane π–π stacking formed at a temperature of 200 °C on graphene, whereas the first crystallites formed with an edge-on orientation at 185 °C on silicon. The crystallization of face-on lamellae revealed two surprising effects during cooling: (a) a constant low value of the π–π spacing below 60 °C; and (b) a reduction by half in the coherence length of face-on lamellae from 100 to 30 °C, which corresponded with the weakening of the 2nd or 3rd order of the in-plane ( k 00) diffraction peak. The final ratio of face-on to edge-on orientations was 40% on graphene, and 2% on silicon, revealing the very different crystallization mechanisms. These results provide a better understanding of how surfaces with different chemistries and intermolecular interactions with the polythiophene polymer chains lead to different crystallization processes and crystallites orientations for specific electronic applications.